2020
DOI: 10.15420/aer.2020.02
|View full text |Cite
|
Sign up to set email alerts
|

A New Era in Zero X-ray Ablation

Abstract: In this article, the authors focus on the importance of the zero X-ray ablation approach in electrophysiology. Radiation exposure related to conventional transcatheter ablation carries small but non-negligible stochastic and deterministic effects on health. Non-fluoroscopic mapping systems can significantly reduce, or even completely avoid, radiological exposure. The zero X-ray approach determines potential clinical benefits in terms of reduction of ionising radiation exposure, as well as safe technical advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…At the same time the growth of technical skill and the awareness of radiation damage have led to a progressive increase of ablative procedures without using fluoroscopy at all. This latter approach in our experience has proved effective, safe, and feasible to ablate almost all types of arrhythmias, as already demonstrated in previous papers ( 11 , 12 ). This is a large study involving a very heterogeneous set of recent procedures performed with the conventional fluoroscopic ablations or by using the zero fluoroscopic approach.…”
Section: Discussionsupporting
confidence: 82%
“…At the same time the growth of technical skill and the awareness of radiation damage have led to a progressive increase of ablative procedures without using fluoroscopy at all. This latter approach in our experience has proved effective, safe, and feasible to ablate almost all types of arrhythmias, as already demonstrated in previous papers ( 11 , 12 ). This is a large study involving a very heterogeneous set of recent procedures performed with the conventional fluoroscopic ablations or by using the zero fluoroscopic approach.…”
Section: Discussionsupporting
confidence: 82%
“…Radiation exposure related to transcatheter ablation carries small but non-negligible stochastic and deterministic effects on health [21,22]. With the development of tools such as 3D mapping systems and intracardiac echocardiography, the current trend is changing towards a non-fluoroscopic approach [23][24][25]. In this study, RFCA and CBA showed fluoroscopy times of 25 and 29 min, respectively.…”
Section: Discussionmentioning
confidence: 79%
“…Follow-up was at center’s discretion but the big majority of patients received at least 3 visits including 12-lead ECG and at least one 24h Holter monitor. Lastly this register did not include any patient performed with a zero X-ray ablation, even when this approach is increasing [ 22 ] and despite the non-negligible effects of X-ray on health [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%